Lysosomal Acid Lipase Deficiency in Libya: A Case Report - Khalid Gashoot,; Muataz Kashbour,; Safa Alfegi,; Asma Berfad, (AlQalam Journal of Medical and Applied Sciences, 2024)
Lysosomal acid lipase deficiency (LAL) is a rare autosomal recessive disorder caused by mutations in the LIPA gene. Wolman disease (WD) is a severe subtype characterized by almost absence of LAL activity. Patients usually present in infancy with gastrointestinal and hepatic manifestations leading to death within the first year of life if left untreated. We report a case of a Libyan infant boy who presented at 3 months of age with persistent vomiting, diarrhea, poor feeding, and failure to thrive. Investigations revealed hypokalemia, hyponatremia, elevated liver enzymes, and abnormal fat in stool. Abdominal imaging showed hepatosplenomegaly, enlarged lymph nodes, and bilateral adrenal calcification suggestive of WD. His condition deteriorated and he succumbed to complications of hepatic failure. Genetic testing confirmed LIPA gene mutation consistent with WD. In conclusion, this study reports the first case of WD in a Libyan infant. Radiological imaging was crucial in identifying specific features of the disease. Unfortunately, the disease progresses rapidly and often results in fatal outcomes in early childhood, highlighting the limited treatment options available for this rare genetic disorder. نقص الليباز حمض الليزوزومي هو اضطراب جسدي متنحي نادر ناجم عن طفرات في جين. نقص الليباز حمض الليزوزومي مرض ولمان هو نوع فرعي حاد يتميز بغياب نشاط الليباز حمض الليزوزومي تقريبًا. عادة ما يصاب المرضى في مرحلة الطفولة بمظاهر معوية وكبدية تؤدي إلى الوفاة خلال السنة الأولى من العمر إذا تركت دون علاج. قمنا بالإبلاغ عن حالة طفل ليبي رضيع ظهر عند عمر 3 أشهر وهو يعاني من القيء المستمر والإسهال وسوء التغذية وفشل النمو. كشفت التحقيقات عن نقص بوتاسيوم الدم ونقص صوديوم الدم وارتفاع إنزيمات الكبد والدهون غير الطبيعية في البراز. أظهر تصوير البطن تضخم الكبد الطحال، وتضخم الغدد الليمفاوية، وتكلس الغدة الكظرية الثنائي مما يوحي بوجود مرض ولمان. تدهورت حالته وتعرض لمضاعفات الفشل الكبدي. أكدت الاختبارات الجينية طفرة جين نقص الليباز حمض الليزوزومي المتوافقة مع مرض ولمان. في الختام، تشير هذه الدراسة إلى الحالة الأولى لمرض ولمان لدى رضيع ليبي. كان التصوير الإشعاعي حاسما في تحديد السمات المحددة للمرض. ولسوء الحظ، يتطور المرض بسرعة وغالباً ما يؤدي إلى نتائج مميتة في مرحلة الطفولة المبكرة، مما يسلط الضوء على خيارات العلاج المحدودة المتاحة لهذا الاضطراب الوراثي النادر